How Do Pensions Affect Corporate Capital Structure Decisions? - Shivdasani, Anil; Stefanescu, Irina (Review of Financial Studies, 2010)
This article examines the capital structure implications of defined benefit corporate pension plans. The magnitude of the liabilities arising from these pension plans is substantial. We show that leverage ratios for firms with pension plans are about 35% higher when pension assets and liabilities are incorporated into the capital structure. We estimate that the tax shields from pension contributions are about a third of those from interest payments. Pension contributions have a modest effect in lowering firms’ marginal corporate tax rates. Once pensions are considered, firms are less conservative in their choice of leverage than has been previously thought. We show that firms incorporate the magnitude of their pension assets and liabilities into their capital structure decisions.